Systemic Perspectives on National Infrastructure for a Sustainable, Resilient Net Zero Future - Dolan, Tom (Frontiers in Built Environment, 2021)
All aspects of Modern life are infrastructure-enabled. National infrastructure (NI) simultaneously: supports the realisation of societally beneficial outcomes; and determines the level of GHG emissions; air, water, noise pollution; production of solid waste and sewage. Therefore, all sustainability and resilience challenges are interdependent emergent properties arising directly or indirectly from National Infrastructure. NI is a systemically, societally, economically, globally significant leverage point. The systemic transformation of NI into a net zero enabling, resilience enhancing, sustainability supporting system is urgently needed to catalyse the speed, scale and breadth of synergistic action needed to achieve Net zero and tackle other sustainability and resilience challenges. Systemic perspectives on, and systemic characterisations of, NI; its societal purpose; and the interdependent mechanisms that enable NI to fulfil its purpose are needed to support the required systemic transformation. This paper provides these. .